Towards the generation of B-cell receptor retrogenic mice - Freitag, Jenny; Heink, Sylvia; Roth, Edith; Wittmann, Jürgen; Jäck, Hans-Martin; Kamradt, Thomas (PLoS ONE, 2014)
Transgenic expression of B- and T-cell receptors (BCRs and TCRs, respectively) has been a standard tool to study lymphocyte development and function in vivo. The generation of transgenic mice is time-consuming and, therefore, a faster method to study the biology of defined lymphocyte receptors in vivo would be highly welcome. Using 2A peptide-linked multicistronic retroviral vectors to transduce stem cells, TCRs can be expressed rapidly in mice of any background. We aimed at adopting this retrogenic technology to the in vivo expression of BCRs. Using a well characterised BCR specific for hen egg lysozyme (HEL), we achieved surface expression of the retrogenically encoded BCR in a Rag-deficient pro B-cell line in vitro. In vivo, retrogenic BCRs were detectable only intracellularly but not on the surface of B cells from wild type or Rag2-deficient mice. This data, together with the fact that no BCR retrogenic mouse model has been published in the 7 years since the method was originally published for TCRs, strongly suggests that achieving BCR-expression in vivo with retrogenic technology is highly challenging if not impossible.
EVALuna2:13620